2016
DOI: 10.1017/s0007114516003706
|View full text |Cite
|
Sign up to set email alerts
|

Food composition tables in resource-poor settings: exploring current limitations and opportunities, with a focus on animal-source foods in sub-Saharan Africa

Abstract: Animal-source foods (ASF) have the potential to enhance the nutritional adequacy of cereal-based diets in low- and middle-income countries, through the provision of high-quality protein and bioavailable micronutrients. The development of guidelines for including ASF in local diets requires an understanding of the nutrient content of available resources. This article reviews food composition tables (FCT) used in sub-Saharan Africa, examining the spectrum of ASF reported and exploring data sources for each refer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 35 publications
(54 reference statements)
0
26
0
1
Order By: Relevance
“…Borrowed data are often from high-income countries’ FCDBs published in the 1960s to 1980s, which have since been updated with higher quality data in the original countries. A recent analysis of animal-source food data from select FCDBs across Sub-Saharan Africa illustrates this point [25]. The authors found that borrowed values comprised as much as 88% of all animal-source food entries in Lesotho, 85% in The Gambia, and 69% in Uganda.…”
Section: The Challenge: Barriers That Impede the Collection And Usmentioning
confidence: 99%
See 2 more Smart Citations
“…Borrowed data are often from high-income countries’ FCDBs published in the 1960s to 1980s, which have since been updated with higher quality data in the original countries. A recent analysis of animal-source food data from select FCDBs across Sub-Saharan Africa illustrates this point [25]. The authors found that borrowed values comprised as much as 88% of all animal-source food entries in Lesotho, 85% in The Gambia, and 69% in Uganda.…”
Section: The Challenge: Barriers That Impede the Collection And Usmentioning
confidence: 99%
“…The limited investment in FCDBs is one of the largest gaps in the dietary assessment research infrastructure of LICs and is cited as a major impediment to analysis and use of individual-level dietary data in this region [10,25]. When national FCDBs do exist, they frequently provide only partial information on critical foods and nutrients, unclear definitions of key nutrients such as vitamin A and, often, inadequate documentation, which precludes any assessment of data quality.…”
Section: The Challenge: Barriers That Impede the Collection And Usmentioning
confidence: 99%
See 1 more Smart Citation
“…A não observância de diferença nas quantidades de vitamina C pode estar associada ao fato de vegetais, em geral, serem boas fontes de vitamina C 18,19 e de os níveis de vitamina C serem reportados como a soma dos . 2019 jan-abr; 12(1): 19-27 -e-ISSN 2176-9206 Artigos Originais países, como é o caso da USDA, pode influenciar na avaliação nutricional de uma dieta, sendo assim, o uso de tabelas que não foram constituídas a partir da análise dos alimentos locais pode apresentar limitações e comprometer a avaliação do consumo alimentar [23][24][25] .…”
Section: Tabelaunclassified
“…Of broader relevance is that this potential is often overlooked, related to lack of data on nutrient composition of indigenous foods, including variation in nutrient content across different species or varieties, particularly in resource-poor settings (de Bruyn et al, 2016). Food-based solutions to dietary problems are often transferred across contexts without sufficient consideration of cultural appropriateness.…”
Section: Broader Relevancementioning
confidence: 99%